مؤشرات تطوير مقررات التربية الإسلامية في كليات التربية - د. طه محمد نور الدائم (White Nile Journal for Studies and Research, 2015)
Abstract: The study in tended to suggest some indicators to develop Islamic studies syllabuses of faculties of education. basic level in Sudan also to clarify misunderstanding concerning this study besides, it wanted to Identify the reasons behind the development of Islamic studies syllabuses. in higher and general education. The major sector concerning the Islamic studies is the value sector Withen the value sector the professional values are considered to be very Important. particularity in educational training centers. The researcher followed the descriptive approach depending on analytical and comparative ways At the end the researcher suggested some indicators supposed to put under consideration when someone prepares Islamic studies syllabuses.